Spontaneous formation of MXene-oxidized sono/chemo-dynamic sonosensitizer/nanocatalyst for antibacteria and bone-tissue regeneration - Yang Yu; Houyi Sun; Qunshan Lu; Junyuan Sun; Pengfei Zhang; Linran Zeng; Krasimir Vasilev; Yunpeng Zhao; Yu Chen; Peilai Liu (Journal of Nanobiotechnology, 2023)
Abstract Prolonged and incurable bacterial infections in soft tissue and bone are currently causing large challenges in the clinic. Two-dimensional (2D) materials have been designed to address these issues, but materials with satisfying therapeutic effects are still needed. Herein, CaO2-loaded 2D titanium carbide nanosheets (CaO2-TiOx@Ti3C2, C-T@Ti3C2) were developed. Surprisingly, this nanosheet exhibited sonodynamic ability, in which CaO2 caused the in situ oxidation of Ti3C2 MXene to produce acoustic sensitiser TiO2 on its surface. In addition, this nanosheet displayed chemodynamic features, which promoted a Fenton reaction triggered by self-supplied H2O2. We detected that C-T@Ti3C2 nanosheets increased reactive oxygen species (ROS) production in response to sonodynamic therapy, which displayed an ideal antibacterial effect. Furthermore, these nanoreactors facilitated the deposition of Ca2+, which promoted osteogenic transformation and enhanced bone quality in osteomyelitis models. Herein, a wound healing model and prosthetic joint infection (PJI) model were established, and the C-T@Ti3C2 nanosheets played a protective role in these models. Taken together, the results indicated that the C-T@Ti3C2 nanosheets function as a multifunctional instrument with sonodynamic features, which might reveal information regarding the treatment of bacterial infections during wound healing. Graphical Abstract